Answer with Step-by-step explanation:
Even function: If f(x)=f(-x)
Then, the function is an even function.
Odd function: If
![f(x)\\eq f(-x)](https://img.qammunity.org/2021/formulas/mathematics/college/4feu41w9lcuevi76k68qh5least47gjv1t.png)
Then, the function is an odd function.
a.
![f(x)=x^5+x](https://img.qammunity.org/2021/formulas/mathematics/college/f969mp93rx6y9a1x250eekxaah7f341tcw.png)
Replace x by -x
![f(-x)=(-x)^5+(-x)=-x^5-x=-(x^5+x)](https://img.qammunity.org/2021/formulas/mathematics/college/jeeg94wyy9wi645pxy9uz006bwx9x7x97b.png)
![f(x)\\eq f(-x)](https://img.qammunity.org/2021/formulas/mathematics/college/4feu41w9lcuevi76k68qh5least47gjv1t.png)
Hence, the function is an odd function.
b.
![g(x)=1-x^6](https://img.qammunity.org/2021/formulas/mathematics/college/708xnua3sckrbt3hll5446ba5mqr9kq7vg.png)
Replace x by -x
![g(-x)=1-(-x)^6=1-x^6](https://img.qammunity.org/2021/formulas/mathematics/college/fztcf7u3vlmpqrdxhqcphz1pr54ldx842q.png)
![g(x)=g(-x)](https://img.qammunity.org/2021/formulas/mathematics/college/3wzwse9dx2nx3ngdyb77790extegr7x76i.png)
Hence, g(x) is an even function.
c.
![h(x)=2x-x^4](https://img.qammunity.org/2021/formulas/mathematics/college/dvsxadu6mi1pmlspz1eeaba6ii44y1k7tb.png)
Replace x by -x
![h(-x)=2(-x)-(-x)^4=-2x-x^4](https://img.qammunity.org/2021/formulas/mathematics/college/o429b5p1lhnqjq79zdcv28juynzsp46wv7.png)
![h(x)\\eq h(-x)](https://img.qammunity.org/2021/formulas/mathematics/college/1ujm5xan1zrfp2x7ecc8k032qqrnxvce8b.png)
Hence, h(x) is an odd function.